ANALISISMAKRO EKONOMI TERHADAP RETURN SAHAM DI BURSA EFEK INDONESIA - Theresia Dhian Kusumawati (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2016)
The changing or developing which occurs in various economic variables of a country willgive impact on the capital market. If an indicator of macro economy is bad, it will give bad impact forthe capital market development. Whereas when an indicator of economy is good, so it will make agood impact on the condition of capital market.Rupiah exchange rate variable, inflation variable, deposit rate variable by partial as well assimultaneous has no significant impact on stock return.